Pendampingan Pengelolaan Administrasi Perpajakan melalui Sistem Administrasi Perpajakan Digital pada BPKPD Kabupaten Pamekasan - Intan Nur Aini; Khy'sh Nusri Leapatra Chamalinda (Jurusan Akuntansi Universitas Trunojoyo Madura, 2026)
Tax administration at BPKPD Pamekasan Regency still faces data discrepancies and inefficient administrative processes. Repeated data verification also affects work efficiency. In addition, the use of the Coretax system has not been fully optimized, so assistance is still needed in its implementation. This community service activity aimed to support tax administration through assistance in digital tax administration based on the Coretax system. The method used was a service learning approach through the MBKM internship program. The activity was carried out through preparation, implementation, monitoring and evaluation, and reporting stages. The results showed that data verification became more systematic. Billing code creation and withholding tax slip preparation became more structured. The use of the Coretax system reduced data input errors. In addition, tax administration became more integrated and digitally documented. This activity improved the efficiency and organization of tax administration within the institution.